(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article teacher to the news flexibility in modern education as an important requirement analysis Science and technologies development education to the system has a significant impact, in front of continuous learning and adaptation task The teacher is putting the news acceptance to do ability not only ensures his professional development but also students quality education to take It also enhances the process. The article discusses, the news flexibility development methods and this process’s importance.